Attacking IEC 61850 Substations by Targeting the PTP Protocol - Akbarzadeh, Aida; Erdodi, Laszlo; Houmb, Siv Hilde; Soltvedt, Tore Geir; Muggerud, Hans Kristian (Electronics (Basel), 2023)
Digital substations, also referred to as modern power grid substations, utilize the IEC 61850 station and process bus in conjunction with IP-based communication. This includes communication with switch yard equipment within the substation as well as the dispatch center. IEC 61850 is a global standard developed to standardize power grid communications, covering multiple communication needs related to modern power grid substations or digital substations. Unlike the legacy communication standards, IEC 60870-5-104 and DNP3, IEC 61850 is specifically designed for IP-based communication. It comprises several communication models and supports real-time communication by introducing the process bus to replace traditional peer-to-peer communication with standard network communication between substation equipment and the switch yard. The process bus, especially Sampled Measured Values (SMV) communication, in modern power grid substations relies on extremely accurate and synchronized time to prevent equipment damage, maintain power grid system balance, and ensure safety. In IEC 61850, time synchronization is provided by the Precision Time Protocol (PTP). This paper discusses the significance and challenges of time synchronization in IEC 61850 substations, particularly those associated with PTP. It presents the results of a controlled experiment that subjects time synchronization and PTP to cyber-attacks and discusses the potential consequences of such attacks. The paper also provides recommendations for potential mitigation strategies. The contribution of this paper is to provide insights and recommendations for enhancing the security of IEC 61850-based substations against cyber-attacks targeting time synchronization. The paper also explores the potential consequences of cyber-attacks and provides recommendations for potential mitigation strategies.